Kuby Immunology - Owen, Judith A. Punt, Jenni (W.H. Freeman and Company, 2013)
The 7th edition of 'Kuby Immunology' presents an up-to-date and comprehensive introduction to the principles and findings of immunology. It contains full-colour illustrations, study questions, study aids and much more.